Variations in template protection by the RNA polymerase II transcription complex during the initiation process. - Cai, H (1987)
Preinitiation complexes (complex 0) or complexes which either made 2 or an average of 10 phosphodiester bonds (complexes 2 and 10, respectively) were assembled in vitro on the adenovirus 2 major late promoter. Each of the complexes was digested extensively with DNase I; the protected DNAs were purified and hybridized in a series of end-labeled oligonucleotides homologous to sequences on the coding or noncoding strands near the initiation site. The hybrids were then extended with reverse transcriptase to map the extent of template protection conferred by proteins in the complex. The downstream protection edge revealed by this approach was approximately +30, +25, and +35 for complexes 0, 2, and 10, respectively. We subsequently found that the apparent inward movement of the downstream protection boundary on initiation could be produced by satisfying the energy requirement for transcription initiation (i.e., by treating with ATP or dATP). The downstream boundary change occurred as rapidly as we could perform the test (less than 60 s) and was not blocked by alpha-amanitin. DNAs from trimmed complexes 0, 2, or 10 all supported extension to a single upstream edge at about position -42. Upstream protection was stable in the preinitiation complex, but when postinitiation complexes were incubated for extended periods, protection of the entire upstream region was lost. This decay of upstream protection, like the movement of the downstream boundary, was found to result from exposure to ATP or dATP. Unlike the downstream boundary movement, however, the upstream change was relatively slow; about 15 min was required to lose one-half of the protection.